PENGARUH CITRA MEREK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN IPHONE - Muhamad Salas Putra; Siti Aminah (STKIP Persada Khatulistiwa Sintang, 2022)
Technological developments in the field of communication are very fast, so that smart phones are created which have quite a lot of uses. In 2007 the big technology company Apple made a breakthrough where Apple launched its first smartphone called the Iphone by running the Iphone OS operating system. The purpose of this study was to analyze the effect of brand image on Iphone purchasing decisions and to analyze the effect of price perceptions on Iphone buying decisions. The sample used was 60 respondents. The research method used in this research is quantitative method. The population in this study were active students of the Faculty of Economics and Business UPN